Job tasks and the participation of low-skilled employees in employer-provided continuing training in Germany. Issue 5 (3rd July 2016) - Mohr, Sabine; Troltsch, Klaus; Gerhards, Christian
Abstract : This study analyses the participation of low-skilled employees in employer-provided training and examines the mechanisms that encourage the training participation of low-skilled employees. Building on theoretical considerations of human capital theory and the task-based approach, we seek to show that job tasks play an important role in explaining different participation levels of low-skilled employees in employer-provided continuing training. The empirical analyses are based on data from the new survey on establishments in Germany. To test the influence of job tasks on participation of low-skilled employees in employer-provided training, we run multivariate regression models that control for other explanatory variables. The results of our analysis confirm that job tasks are relevant to changes in the participation rates of low-skilled employees, which leads to the conclusion that differences between job tasks affect employers' willingness to invest in training for their low-skilled staff.